Calcium application enhances growth and alleviates the damaging effects induced by Cd stress in sesame (Sesamum indicum L.). Issue 1 (1st January 2017) - Abd_Allah, Elsayed Fathi; Hashem, Abeer; Alqarawi, Abdulaziz A.; Wirth, Stephan; Egamberdieva, Dilfuza
ABSTRACT: In this study, the effects of calcium (Ca 2+ ) application on acquired systemic tolerance mechanism to cadmium (Cd) stress in sesame ( Sesamum indicum L.) were studied. The Cd stress reduced the root and shoot growth of sesame, and plant contents of photosynthetic pigments; however, the application of Ca 2+ improved these parameters under Cd stress condition. The hydrogen peroxide, malondialdehyde and soluble sugar contents were higher under Cd stress, and were reduced by Ca 2+ treatment. The antioxidant enzyme activities in the leaves of sesame, superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR) were higher under Cd stress, whereas reduced concentration was observed in Ca 2+ -treated plants. Cd stress increased the contents of diacylglycerol and sterol ester; however Ca 2+ treatment resulted in a significant increase in phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol and phosphatidylserine. Our results indicated that application of calcium enables sesame plants to withstand the deleterious impact of cadmium through upregulating acquired systemic tolerance system as lipid fractions (galactolipids, phospholipids, neutral lipids), antioxidant enzymes (SOD, POD, CAT, APX, GR) hence protect membrane functions.